1991
DOI: 10.1007/bf00176873
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the last highstand of Lake Lahontan

Abstract: Radiocarbon and uranium-series ages of a variety of materials from the Lahontan basin indicate that the last highstand lake occurred between 14 500 and 13 000 yr B.P. Although few in number, existing radiocarbon and uranium-series age data also indicate that lakes in the western Lahontan subbasins were small or moderate in size between 30000 and 25 000 yr B.P. Existing data do not support the conclusions of Bradbury et al. (1989) who did not find evidence of a 14000 + yr B.P. highstand lake in the sediments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The late Quaternary highstand of Lake Lahontan occurred between 14,500 and 13,000 years BP (Benson, 1991). The lake probably retreated from the study area by about 9500 years BP (Benson et al, 1990(Benson et al, , 1992.…”
Section: Quinn River Nevadamentioning
confidence: 93%
“…The late Quaternary highstand of Lake Lahontan occurred between 14,500 and 13,000 years BP (Benson, 1991). The lake probably retreated from the study area by about 9500 years BP (Benson et al, 1990(Benson et al, , 1992.…”
Section: Quinn River Nevadamentioning
confidence: 93%
“…Researchers have suggested that the stratigraphic record of other lakes within the Great Basin also have evidence of oscillations during the end of the Last Glacial Maximum (i.e., Lake Lahontan (Benson, 1991), Lake Russell (Benson et al, 1998), Lake Estancia (Anderson et al, 2002), and Lake Franklin (Munroe and Laabs, 2013)). However, the published records of these lakes are not extensive enough to understand if the timing and magnitude of proposed oscillations correlate across basins and specifically to the oscillations of this study.…”
Section: Climatic Implicationsmentioning
confidence: 98%
“…The drier conditions on Huascarán (9°S) and wetter conditions on Sajama (18°S) are consistent with LGS lake-level reconstructions (StreetPerrott and Harrison, 1984), when only 25% of the tropical lakes that have been studied were as high as today. In the Northern Hemisphere between 25°and 35°N, most of the lakes were higher than today (Benson, 1981(Benson, , 1991Broecker et al, 1998;Grove, 1976, 1979). Model experiments (Rind, 1998) suggest that this difference in lake levels is consistent with a reduction in the tropical latitudinal temperature gradient and in Hadley Cell intensity.…”
Section: The Sajama (Bolivia) Ice-core Historymentioning
confidence: 99%